Hubungan Leader Member Exchange dan Kepuasan Kerja dengan Komitmen Organisasi pada Tenaga Pendidik Sekolah Polisi Negara Kepolisian Daerah Sumatera Utara - Wahyu Sukoco; M.Rajab Lubis; Hasanuddin Hasanuddin (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This study aims to see the relationship between Leader Member Exchange and Job Satisfaction with Organizational Commitment to North Sumatra Police State Police School Educators. The study was conducted on 75 educators. Data collection is a scale method, namely the Leader Member Exchange scale, the scale of job satisfaction and the scale of organizational commitment. Before the scale was used, a scale trial was carried out on 40 civil servants / civil servants. Data were analyzed using Multiple Regression. The results showed; There is a very significant relationship between leader member exchange and job satisfaction with organizational commitment. Based on the results of this study, it can be stated that the hypothesis proposed in this study is accepted. The two variables in this study, namely leader member exchange and job satisfaction on organizational commitment, contributed 84.8% to the level of organizational commitment. Separately, the leader member exchange contributed 66.9% to the level of organizational commitment, while job satisfaction contributed 83.3% to the level of organizational commitment. The total contribution of the two independent variables to the dependent variable was 84.8%. This means that there are still 15.2% of the influence of other variables on organizational commitment, including personal or individual factors including quality of work life, organizational factors in the form of organizational climate, and non-organizational factors.